170k views
0 votes
HELPPPPPPPPPPP PLEASE ASAP

What is (f−g)(x)?



f(x)=x4−3x2+5x−7

g(x)=x3−3x2+3x−1

Enter your answer, in standard form, in the box.

(f−g)(x)=

User Jose Jet
by
5.6k points

1 Answer

4 votes

Answer:


(f-g)(x)=x^(4)-x^(3)+2x-6

Explanation:

1- You have the following fucntion given in the problem:


f(x)=x^(4)-3x^(2)+5x-7\\g(x)=x^(3)-3x^(2)+3x-1

2. To solve this exercise you only need to subtract
f(x) and
g(x), as following:

- Multiply signs.

- Add the like terms.

Then:


(f-g)(x)=(x^(4)-3x^(2)+5x-7)-(x^(3)-3x^(2)+3x-1)\\(f-g)(x)=x^(4)-3x^(2)+5x-7-x^(3)+3x^(2)-3x+1\\(f-g)(x)=x^(4)-x^(3)+2x-6


User Bogdan Stoica
by
6.5k points